Behavioral insights into audience satisfaction: analyzing emotional and cognitive factors in K-culture dance engagement - Hyesung Yun; Miyoung Park; Chang Hwan Choi (PLoS ONE, 2025)
Despite growing interest in Korean traditional dance through the Korean Wave (Hallyu), empirical research on audience satisfaction remains limited. This study examines how personal orientation, emotional/cognitive responses, and environmental factors influence audience satisfaction, grounded in Expectancy-Disconfirmation Theory and the Tripartite Model of Attitude. We surveyed 272 audience members (65.8% male; ages 20–59) attending a Korean traditional dance performance using a validated 20-item questionnaire (Cronbach’s α ≥ 0.78). Data collection included IRB approval, informed consent, pilot testing (N = 45), and comprehensive validity testing. Multiple regression analysis revealed that cognitive appreciation (β = 0.368, p < 0.001), emotional response (β = 0.289, p < 0.001), and environmental quality (β = 0.357, p < 0.001) collectively explained 72% of variance in satisfaction. Gender showed weak effects (β = 0.02, p < 0.05), while age, marital status, and occupation were non-significant. Quantile regression confirmed robust effects across all satisfaction levels. This research advances audience satisfaction theory by demonstrating that psychological experiences—not demographics—drive satisfaction universally across audience groups. The strong environmental effect in this Korean context suggests cultural contingencies in aesthetic experience. These findings provide theoretical insights and practical guidance for enhancing traditional performing arts experiences, though single-event sampling and self-report limitations necessitate future multi-site longitudinal research.